NASKAH DOKUMEN/SURAT RAJA KESULTANAN KALIMANTAN BARAT: KAJIAN STRUKTUR, PALEOGRAFI, DAN KEBAHASAAN (Royal Letter/Document of West Kalimantan Sultanate: Structure, Paleography, and Language) - Muhammad Jaruki (Kantor Bahasa Sulawesi Tenggara, 2017)
Issues disclosed in the research are the structure, the form and style, and language aspect used in Royal Letter/Document of Pontianak Sultan, West Kalimantan Sultanate. The aim of the research is to discribe and explain structure, the style of writing of Jawi script, and the language used in the script or letter of “Sultan Pontianak, Sultan Syarif Hamid Bin Sultan Syarif U'sman Alqodri to the Government of the Netherlands”. Using content analysis method to describe the structure, style, and language contained in those scripts, and diplomatic method for manuscript editing, the edited text produced is in accordance with the original. The analysis result shows that the script of